«I am getting better» and «I feel good»: searching for an objective criterion for a clinical response to analgesic therapy for rheumatic diseases - A. E. Karateev; E. Yu. Pogozheva; V. N. Amirdzanova; E. S. Filatova; V. A. Nesterenko (Современная ревматология)
Analysis of the results of clinical trials should be based on the use of objective parameters that allow for assessing the significance of the data obtained for real medical practice. These parameters include Minimal Clinically Important Improvement (MCII) and Patient Acceptable Symptom State (PASS).Objective: to determine the approximate value of the parameters MCII and PASS on the basis of data from the PARACELS (Regular Piascledine and Artrosilene Administration for osteoarthritis (OA): Expediency of the Unified Treatment Regimen) study.Patients and methods. A study group consisted of 6,448 patients (70.9% female, 29.1% male) (mean age, 57.8±10.2 years) with knee OA and moderate or severe pain of ≥40 mm on a 100-mm visual analogue scale (VAS). All the patients took during 12 weeks avocado/soybean unsaponifiables 300 mg/day and a nonsteroidal anti-inflammatory drug (ketoprofen lysine salt) 320 mg/day, which was prescribed at the beginning of treatment for 10–14 days and then could be used on demand with more pain to come. Pain intensity was measured using the 100-mm VAS. Patient satisfaction with treatment results was also studied with a point scale, where 0 is worsening or no effect, while 5 is an excellent effect. The dynamics of pain was compared and treatment results were assessed by patients.Results and discussion. After 12 weeks, most patients showed a substantial improvement: a mean pain intensity reduction of 77.7±29.6%. A satisfactory treatment result estimate (that can be considered as a surrogate measure of MCII) corresponded to an average pain reduction of 32.0±11.7 mm on VAS (a 47.3% improvement compared to the baseline level). A good treatment result estimate (that can be considered as a surrogate measure of PASS) corresponded to an average pain reduction of 41.0±13.3 mm on VAS (a 62.9% improvement compared to the baseline level).Conclusion. The PARACELS study has shown that in Russian patients receiving analgesic therapy, MCII can correspond to a pain reduction of >30 mm on VAS (>40% of the baseline level), PASS can do to its reduction of >40 mm on VAS (>60% of the baseline level).